Does passive smoking increase the frequency of health service contacts in children with asthma?. Issue 1 (1st January 2001) - Crombie, I K; Wright, A; Irvine, L; Clark, R A; Slane, P W
Abstract : BACKGROUND: Passive smoking is a major cause of respiratory morbidity in children. However, few studies give accurate estimates of the health effects of passive smoking in children with asthma using an objective measure of exposure. The effects of passive smoking using salivary cotinine levels to measure exposure were investigated. METHODS: A sample of 438 children aged 2–12 years with asthma who had a parent who smoked were recruited in Tayside and Fife, Scotland. Health service contacts for asthma, assessed from GP case records, were used as a proxy for morbidity. RESULTS: A weak U-shaped relationship was found between the salivary cotinine level and health service contacts for asthma: compared with low cotinine levels those with moderate cotinine levels had a reduced contact rate (relative rate (RR) = 0.91, 95% confidence interval (CI) 0.80 to 1.05), whereas high cotinine levels were associated with an increased rate of contact (RR = 1.19, 95% CI 1.05 to 1.37). In contrast, a strong association was seen with the amount the parent reported smoking in front of the child: the higher the level the fewer visits were made for asthma (RR for everyday exposure = 0.66, 95% CI 0.56 to 0.77). This effect was not seen for non-respiratory visits. Demographic factors, age of child, and number of children in the family all had a powerful effect on the number of visits for asthma. The parents' perception of asthma severity was associated with visit frequency independent of actual severity (derived from drug treatment). CONCLUSION: High levels of parental smoking in the home are associated with a reduction in health care contacts for asthma. This could be due to a lack of awareness of asthma symptoms among heavy smokers or a reluctance to visit the GP. Children with asthma who have parents who smoke heavily may not be receiving adequate management.